2019
DOI: 10.1002/ange.201911544
|View full text |Cite
|
Sign up to set email alerts
|

Barcoding Biological Reactions with DNA‐Functionalized Vesicles

Abstract: Targeted vesicle fusion is a promising approach to selectively control interactions between vesicle compartments and would enable the initiation of biological reactions in complex aqueous environments. Here, we explore how two features of vesicle membranes, DNA tethers and phase‐segregated membranes, promote fusion between specific vesicle populations. Membrane phase‐segregation provides an energetic driver for membrane fusion that increases the efficiency of DNA‐mediated fusion events. The orthogonality provi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…Also, the properties of the vesicles are related to the sequence of DNA, e.g., the fusion between vesicles can be promoted by the presence of DNA. [197][198][199] Alternatively, DNA amphiphiles can be used to regulate cell-to-cell interactions through the anchoring of hydrophobic moieties and molecular hybridization of DNA. [200][201][202] In another work, Park et al reported that two amphiphilic block copolymers, poly(butadiene)-block-poly(ethylene oxide) (PBD-b-PEO) and polymethyl acrylate-block-DNA (PMA-b-DNA), could coassemble to form giant polymersomes ( Figure 20D); when two of this kind of polymersomes interacted via strand-hybridization, the DNA that originally uniformly distributed on the polymersome would gather to one side and form a DNA island.…”
Section: Vesicle-dna Amphiphile Complexmentioning
confidence: 99%
“…Also, the properties of the vesicles are related to the sequence of DNA, e.g., the fusion between vesicles can be promoted by the presence of DNA. [197][198][199] Alternatively, DNA amphiphiles can be used to regulate cell-to-cell interactions through the anchoring of hydrophobic moieties and molecular hybridization of DNA. [200][201][202] In another work, Park et al reported that two amphiphilic block copolymers, poly(butadiene)-block-poly(ethylene oxide) (PBD-b-PEO) and polymethyl acrylate-block-DNA (PMA-b-DNA), could coassemble to form giant polymersomes ( Figure 20D); when two of this kind of polymersomes interacted via strand-hybridization, the DNA that originally uniformly distributed on the polymersome would gather to one side and form a DNA island.…”
Section: Vesicle-dna Amphiphile Complexmentioning
confidence: 99%
“…They also found that longer DNA strands increased vesicle docking but failed to lead to vesicle fusion. Recently, Peruzzi et al showed the initiation of CFE by DNA-mediated vesicle fusion and found that phase-segregation of membrane domains enhances fusion between different vesicle populations (Figure 3B) [121]. Controlling fusion by using DNA-tethered vesicles provides exquisite specificity and expands the opportunities to control spatiotemporal dynamics of CFE reactions.…”
Section: Dna-mediated Fusionmentioning
confidence: 90%
“…(B) Complementary DNA strands on two different vesicles eventually lead to their fusion and allow mixing of the contents.This can be utilized to initiate any biochemical reactions, such as in vitro protein synthesis. Reproduced from Reference[121] with permission from John Wiley and Sons, copyright 2019. (C) Schematic diagram of coiled-coil peptide-mediated vesicle fusion.…”
mentioning
confidence: 99%
“…19 In this approach DNA motifs are anchored to the surface of synthetic membranes (typically liposomes) through hydrophobic modifications, including cholesterol, tocopherol and lipids. [20][21][22][23][24][25][26] Zipping between complementary strands anchored on the surface of two different membranes then triggers their fusion, 21,[27][28][29] the efficiency of which has been found to depend on both DNA-nanostructure design and composition and lateral organisation of the bilayers. 27,28,30 For example, membrane fusion was maximised when DNA zippers were equipped with two hydrophobic anchors, rather than a single one, reportedly because of the higher stability of the DNA-vesicle interaction, 30 and when minimising the length of the linker connecting the hydrophobic moiety (cholesterol) to the DNA.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26] Zipping between complementary strands anchored on the surface of two different membranes then triggers their fusion, 21,[27][28][29] the efficiency of which has been found to depend on both DNA-nanostructure design and composition and lateral organisation of the bilayers. 27,28,30 For example, membrane fusion was maximised when DNA zippers were equipped with two hydrophobic anchors, rather than a single one, reportedly because of the higher stability of the DNA-vesicle interaction, 30 and when minimising the length of the linker connecting the hydrophobic moiety (cholesterol) to the DNA. 31 Additionally, the extent of DNA-induced lipid mixing was shown to be impacted by the incorporation of cholesterol and phosphatidylethanolamine (PE) lipids 28 or by changes in the lateral organisation of the membrane.…”
Section: Introductionmentioning
confidence: 99%